The threshold between life and death in Cistus albidus L. seedlings: mechanisms underlying drought tolerance and resilience. (16th April 2021) - Pérez-Llorca, Marina; Caselles, Vicent; Müller, Maren; Munné-Bosch, Sergi
Abstract: Drought can lead to important shifts in population dynamics if it occurs during seedling establishment. With the aim of elucidating the underlying mechanisms of drought tolerance and resilience, here we monitored the survival of seedlings of the Mediterranean shrub Cistus albidus L. throughout a year growing in the natural Park of the Montserrat Mountains (Spain) and, additionally, we studied the response to severe drought and subsequent recovery after rewatering of seedlings grown in growth chambers. To find possible mechanisms explaining how seedlings respond to drought, growth and survival together with physiological-related parameters such as chlorophyll contents, vitamin E and stress-related phytohormones were measured. We found that survival decreased by 30% at the end of summer and that the main proxy of seedling survival was total chlorophyll. This proxy was further confirmed in the growth chambers, where we found that seedlings that recovered from drought had higher levels of total chlorophyll compared with the seedlings that did not recover. Furthermore, modulation of vitamin E and jasmonates contents appeared to be crucial in the drought response of C. albidus seedlings. We propose a prediction model of survival that includes total chlorophyll height, leaf mass area and maximum photosystem II efficiency with chlorophyll contents being a good long-term predictor of C. albidus seedling survival under severe stress, which, in turn, could help to better foresee population fluctuations in the field.